The Effectiveness of Customized Courseware in Teaching Grammar - Faizah, Mohamad; Nazen, Mohamad Amin (INTI University College, 2009)
The widespread use of computer courseware in numerous fields and domains has given quite an impact on education especially on the second and foreign language education. With the advent of technologies, courseware with multimedia elements and interactive contents has emerged to assist English language teaching. Since teachers are considered as the guardians of the classrooms. It Is Important to Look into another alternative as a potential assistance to language learning that courseware can offer. However, most readily available courseware in the market are not tailored to the needs of the Local young Malaysian learners. Therefore, this study is to investigate whether a customized courseware specially developed for young learners is effective in teaching specific grammatical items. The study Involved 40 young learners in Year 5 at one of the primary schools in the state of Terengganu, Malaysia. A quasi experimental study was conducted in which 20 learners were put in an experimental group and another 20 learners were put in a control group. The experimental group was exposed to a customized courseware developed based on the syllabus in the teaching of grammatical items and the control group was taught using a traditional method that is using chalk and board and flash cards. A pre-test was administered prior to the treatment and a post-test was administered after the treatment to both groups. The target structures under investigation were past tense and present tense. Under past tense structure, it was further divided into the use of regular and irregular verbs. There were also two components under present tense structure, which were simple and complex structures. The findings showed that generally the: customized courseware was effective in leaching grammar. It also found that the effectiveness varied depending on the structures taught. For example, the customized courseware was found effective in the teaching of past tense as compared to the teaching of present tense. The learners in the experimental group also fared better in the irregular verbs as compared to the regular verbs. Nevertheless, the teaching V of simple and complex structures by using computer was as effective as teaching the structures by using traditional methods. Since the customized courseware had the potential in improving the learners’ knowledge of grammar, it can be considered as an aid to further capacitating the Learners to deal with b future Learning situations. Furthermore1 the rote of the teachers might not be merely as the instructors, but they can be the instructional courseware designers who can always find new innovative ways to help learners become better language learners.